Study of fungal rhinosinusitis - Padmavathi Devi Chaganti; Natta B Rao; Karri M Devi; B Janani; Pamidipalli V Vihar; Govada Neelima (Journal of Dr. NTR University of Health Sciences, 2020)
Background: Rhinosinusitis is a common disorder occurring in 20% of the population. Chronic sinus infection unresponsive to antibiotics should raise the suspicion of Fungal rhinosinusitis. Various types of fungi caused inflammation of sinus mucosa. Aims and Objectives: Thepresent studywas undertakento determine the etiology, clinical features, and diagnosis of Fungal Rhinosinusitis. Material and Methods: Twenty cases of rhinosinusitiswere studied in two years period in a tertiary care hospital. Specimens collected were processed with paraffin processing andstained with H and E stain. Special stains for Fungus were done in all cases. Results: Cases of Rhinosinusitis were mostly seen in the 5th decade with femalepreponderance. All the cases were non-invasive and Maxillary sinus was involved in majority of cases. Aspergillus was identified in majority of cases followed by Candida. Mucor mycosis was seen in diabetics. Conclusion: In the present study, all the cases of rhinosinusitis are non-invasive. A special stain for Fungus helps in identifying the type of organism.